Difficulties in the diagnosis of periapical translucencies and in the classification of cemento-osseous dysplasia - Andrea Brody; Attila Zalatnai; Krisztian Csomo; Andrea Belik; Csaba Dobo-Nagy (BMC, 2019)
Abstract Background Cemento-osseous dysplasia is a benign fibro-osseous lesion of the tooth-bearing region of the jaws with a periodontal ligament origin. It appears predominantly in Black and Asian middle-aged females. Its importance is that it could mimic a periapical lesion in the early, translucent stage. Case presentation In this report a rare case of familial cemento-osseous dysplasia is presented: a 50-years old Caucasian woman with labial paraesthesia and radiological translucency around the roots of the mandibular incisors and the first molar teeth. The lesion around the first molar was diagnosed as periapical granuloma and a root canal treatment was carried out. The diagnosis of florid cemento-osseous dysplasia and the treatment plan based on two- and three-dimensional radiographic examinations were certified histologically after surgical removal of the lesion. We screened the family members - including the patient's mother, daughter and son - and identified a periapical version of cemento-osseous dysplasia in the daughter. Our case highlights the difficulties of differential diagnosis of cemento-osseous dysplasia and other periapical pathologies. The inconsistencies in the present classification of cemento-osseous dysplasia are also discussed with a proposal for a different classification based on new aspects that would be very helpful in setting up a correct treatment plan. Conclusion Differentiation of endodontic and non-endodontic origin of radiolucency and distinguishing it from anatomical landmarks by appropriate clinical evaluation and using vitality testing can give an opportunity to prevent unnecessary endodontic treatment.The current categories of cemento-osseous dysplasia classification do not cover the early stage of a hereditary florid form of cemento-osseous dysplasia.Instead of anatomical location of the lesion, clinical and genetic features may be recommended as parameters of cemento-osseous dysplasia classification.